PSYCHOLOGICAL DEPTH AND CHARACTERIZATION IN OATES’ NOVELS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article gives information about the multidimensional psychological depth and complex characterization in Joyce Carol Oates’ novels, emphasizing how her narrative strategies illuminate the inner turmoil, fragmented identities, and existential anxieties of her protagonists. Through close textual analysis of selected works such as Blonde, You Must Remember This, and Black Water, the study reveals how Oates employs stream of consciousness, symbolic motifs, Gothic undertones, and trauma-centered narrative structures to portray the instability of the human psyche. The article argues that Oates’ characters embody the psychological tensions of contemporary American society, where personal trauma, sociocultural pressures, and moral ambiguity shape individual consciousness. By examining the interplay between internal conflict and external forces, the research demonstrates that Oates’ unique approach to character construction not only deepens emotional resonance but also advances a broader critique of power, violence, and vulnerability in modern life.